2020
DOI: 10.2174/1871530319666191022100141
|View full text |Cite
|
Sign up to set email alerts
|

Diet: A Source of Endocrine Disruptors

Abstract: Background: Food is indispensable for human life and determines the health and wellbeing of the consumer. As food is the source of energy for humans, it also emerges as one of the most important sources of exposure to deleterious chemicals both natural and synthetic. The food exposed chemicals cause a number of detrimental health effects in humans, with endocrine disruption being of serious concern amongst these effects. Such chemicals disrupting the health of endocrine system are known as endocrine-disruptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 155 publications
0
18
0
Order By: Relevance
“…Indeed, EDCs are contained in these products (e.g., phenols and phthalates) and can be transferred especially to warm foods [41,42]. Consumption of packaged meat/vegetables was also considered a habit at risk as it can be a source of exposure to phthalates and bisphenols [43,44]. In addition, the use of personal care products, which may contain phthalates and parabens [45], was evaluated as a habit that can increase EDC exposure [15].…”
Section: Edc Exposurementioning
confidence: 99%
“…Indeed, EDCs are contained in these products (e.g., phenols and phthalates) and can be transferred especially to warm foods [41,42]. Consumption of packaged meat/vegetables was also considered a habit at risk as it can be a source of exposure to phthalates and bisphenols [43,44]. In addition, the use of personal care products, which may contain phthalates and parabens [45], was evaluated as a habit that can increase EDC exposure [15].…”
Section: Edc Exposurementioning
confidence: 99%
“…Among them, xenoestrogens are receiving attention due to their biological action and ubiquitous human chronic exposure through their release into beverages, food, and the environment [11][12][13]. Xenoestrogens are synthetic or natural chemical compounds that have the ability to mimic estrogen and have estrogenic effects on biological organisms, thus interfering with the estrogen produced by the endocrine system.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified the health problems associated with synthetic xenoestrogens that are found in various materials, including additives or contaminants in food [21][22][23]. These endocrine-disrupting chemicals have become a part of everyday life, interfere with the natural cycle of the hormones in the body, and are thought to give rise to many endocrine-related disorders, including endocrine-related cancers.…”
Section: Discussionmentioning
confidence: 99%